Mobile robots for dynamic environments - Kececi, Emin Faruk; Ceccarelli, Marco (Automation and control collection., 2015)
One key point for mobile robots is interaction with the environment in which the mobile robot moves and corresponding solutions can determine the success or failure of the motion. Indeed, the mechanical design is not very often considered a critical issue, but rather it is often included as an issue in the overall design of mechanical solutions within servo-controlled operation and environment interaction. A second important issue is the acceptance of robotic systems and the corresponding psychological aspects, when robots are proposed to operators and users in fields with very low levels of technical means in their current work practice. These two subjects are the core of the discussions in this book, which aims to illustrate not only the potential but also the problems for the dissemination of mobile robots and mobile robotic systems in all human activities with service aims.